2021
DOI: 10.1029/2021gl094901
|View full text |Cite
|
Sign up to set email alerts
|

Earthquake Nucleation Along Faults With Heterogeneous Weakening Rate

Abstract: suggest one possible scenario where the onset of fault motion is characterized by the transition from quasistatic slip growth to dynamic rupture propagation (Passelègue et al., 2016;Svetlizky et al., 2016). The transition happens when a region of critical size 𝐴𝐴 𝐴𝐴c of the fault is slipping. The knowledge of this nucleation length proves crucial since it allows to predict both the loading levels and the position at which the earthquake motion starts (Albertini et al., 2020;Ampuero et al., 2006;Uenishi & R… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 50 publications
2
30
0
Order By: Relevance
“…Capturing these effects would require more complex physics and in particular more advanced friction formulations such as rate and state or mechanistic models. Also, slip is known to be governed by local fluctuations in friction properties, both at small scales (Luo & Ampuero, 2018;Lebihain et al, 2021) and at larger scales because friction properties are lithology-dependent (Hunfeld et al, 2017). More advanced friction formulations and heterogeneities in friction properties can be implemented relatively straightforward in the current formulation.…”
Section: Discussionmentioning
confidence: 99%
“…Capturing these effects would require more complex physics and in particular more advanced friction formulations such as rate and state or mechanistic models. Also, slip is known to be governed by local fluctuations in friction properties, both at small scales (Luo & Ampuero, 2018;Lebihain et al, 2021) and at larger scales because friction properties are lithology-dependent (Hunfeld et al, 2017). More advanced friction formulations and heterogeneities in friction properties can be implemented relatively straightforward in the current formulation.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, for slip-weakening friction, we can use LSA to compute the universal nucleation length for any non-uniform loading condition [3,20,[22][23][24]. Uenishi and Rice [20] showed that starting from the equation for quasi-static elastic equilibrium (Eq.…”
Section: Stress Criterionmentioning
confidence: 99%
“…Previous numerical works on nucleation of frictional sliding have mostly focused on the yielding phase, either because residual friction is disregarded [20] or simply because it is not triggered during nucleation [23,24]. Other works that do trigger residual friction concentrate mainly on the effect of background stress and pore pressure [25][26][27][28], while some others explore the role of heterogeneity but are still limited to a single source [29][30][31] or focus exclusively on the quasi-static features of nucleation [16,32], missing out on the rich dynamics of late nucleation mechanisms triggered by the onset of fracture.…”
Section: Introductionmentioning
confidence: 99%
“…1c, d). The general existence of heterogeneous fault structure and pre-existing stress may lead to multiple rupture fronts nucleating simultaneously from several asperities (Lebihain et al, 2021;Dublanchet et al, 2013;Mai and Beroza, 2002;Campillo et al, 2001), complex collective slip fronts in 3D, jumps of the rupture front, and repeated acceleration and deceleration of the failure process. Source time functions of earthquakes are frequently complex, showing multiple peaks that re ect these processes.…”
Section: Field Studiesmentioning
confidence: 99%